2016
DOI: 10.1007/s40333-016-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of satellite-derived grassland vegetation phenology from 1998 to 2012 in Inner Mongolia, China

Abstract: Spatio-temporal variations of vegetation phenology, e.g. start of green-up season (SOS) and end of vegetation season (EOS), serve as important indicators of ecosystems. Routinely processed products from remotely sensed imagery, such as the normalized difference vegetation index (NDVI), can be used to map such variations. A remote sensing approach to tracing vegetation phenology was demonstrated here in application to the Inner Mongolia grassland, China. SOS and EOS mapping at regional and vegetation type (mead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
(101 reference statements)
1
20
0
1
Order By: Relevance
“…The unusually low precipitation during the late spring of 2015 (the average calculated PET from May to July was 0.7 ± 0.4), which induced a homogeneous drying of the soil across all soil warming levels (data not shown), thus likely delayed the greenup beyond the timing of “GDD fulfillment.” This can explain the higher cumulative GDD at SOS. This delaying effect of spring drought to the timing of SOS agreed with earlier studies of subarctic grasslands (Chen et al., ) and of grasslands in general (Sha et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The unusually low precipitation during the late spring of 2015 (the average calculated PET from May to July was 0.7 ± 0.4), which induced a homogeneous drying of the soil across all soil warming levels (data not shown), thus likely delayed the greenup beyond the timing of “GDD fulfillment.” This can explain the higher cumulative GDD at SOS. This delaying effect of spring drought to the timing of SOS agreed with earlier studies of subarctic grasslands (Chen et al., ) and of grasslands in general (Sha et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the considerable difference in the timing of earliest greening in 2013 and 2014 (beginning of May) versus 2015 (beginning of June), in combination with the clear decline in temperature sensitivity in 2015, indicated that day length was not the main driver of the SOS in these subarctic grasslands. Precipitation can play a role in SOS of subarctic and alpine grasslands, although its effect is not consistent, varying between nonexistent (Piao et al., ), positive (Fu, Piao, et al., ), negative (Chen et al., ; Sha, Zhong, Bai, Tan, & Li, ), and dependent on the specific situation (Shen, Piao, Cong, Zhang, & Janssens, ; Shen, Tang, Chen, Zhu, & Zheng, ; Zhang, Yi, Kimball, Kim, & Song, ). In this study, no major variation in soil water status occurred along the temperature gradients (Sigurdsson et al., ), especially in early spring, so it is unlikely that precipitation was an important determinant of the decelerating advance of SOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Miao et al () found an advanced SOS and a delayed EOS across the biomes in Monglian Plateau (consists of both Inner Mongolia of China and the Republic of Mongolia, the Inner Mongolia is located in the eastern and southern parts of Mongolian Plateau). By contrast, Sha et al () reported that both SOS and EOS did not exhibit consistent shifts at the regional scale in Inner Mongolian grasslands. In general, existing studies are mainly based on satellite greenness index data and spatially interpolated climate data.…”
Section: Introductionmentioning
confidence: 89%
“…A significant advancement in the first leaf unfolding of T. mongolicum during the period 1990-2009 was observed at nine stations, while a significant delay was found at seven stations in east China (Chen et al, 2015). In addition to ground-based studies, the remote sensing data also indicated that the start of the growing season did not exhibit consistent shifts at either the regional or vegetation type level in Inner Mongolia from 1998 to 2012 (Sha et al, 2016;Ren et al, 2018). These results differed from the widespread earlier spring events of all plants and animals in China (Ge et al, 2015).…”
Section: Discussionmentioning
confidence: 90%